Multidimensional analysis of tumor stem cells: from biological properties, metabolic adaptations to immune escape mechanisms - Han, Han; He, Ting; Wu, Yingfan; He, Tianmei; Zhou, Weiqiang (Frontiers in Cell and Developmental Biology, 2024)
As a key factor in tumorigenesis, progression, recurrence and metastasis, the biological properties, metabolic adaptations and immune escape mechanisms of CSCs are the focus of current oncological research. CSCs possess self-renewal, multidirectional differentiation and tumorigenicity, and their mechanisms of action can be elucidated by the clonal evolution, hierarchical model and the dynamic CSCs model, of which the dynamic model is widely recognized due to its better explanation of the function and origin of CSCs. The origin hypothesis of CSCs involves cell-cell fusion, horizontal gene transfer, genomic instability and microenvironmental regulation, which together shape the diversity of CSCs. In terms of classification, CSCs include primary CSCs (pri-CSCs), precancerous stem cells (pre-CSCs), migratory CSCs (mig-CSCs), and chemo-radiotherapy-resistant CSCs (cr-CSCs and rr-CSCs), with each type playing a specific role in tumor progression. Surface markers of CSCs, such as CD24, CD34, CD44, CD90, CD133, CD166, EpCAM, and LGR5, offer the possibility of identifying, isolating, and targeting CSCs, but the instability and heterogeneity of their expression increase the difficulty of treatment. CSCs have adapted to their survival needs through metabolic reprogramming, showing the ability to flexibly switch between glycolysis and oxidative phosphorylation (OXPHOS), as well as adjustments to amino acid and lipid metabolism. The Warburg effect typifies their metabolic profiles, and altered glutamine and fatty acid metabolism further contributes to the rapid proliferation and survival of CSCs. CSCs are able to maintain their stemness by regulating the metabolic networks to maintain their stemness characteristics, enhance antioxidant defences, and adapt to therapeutic stress. Immune escape is another strategy for CSCs to maintain their survival, and CSCs can effectively evade immune surveillance through mechanisms such as up-regulating PD-L1 expression and promoting the formation of an immunosuppressive microenvironment. Together, these properties reveal the multidimensional complexity of CSCs, underscoring the importance of a deeper understanding of the biology of CSCs for the development of more effective tumor therapeutic strategies. In the future, therapies targeting CSCs will focus on precise identification of surface markers, intervention of metabolic pathways, and overcoming immune escape, with the aim of improving the relevance and efficacy of cancer treatments, and ultimately improving patient prognosis.